2019
DOI: 10.1094/pdis-07-18-1201-re
|View full text |Cite
|
Sign up to set email alerts
|

Host Range and Genetic Characterization of Ditylenchus dipsaci Populations from Eastern Canada

Abstract: The stem and bulb nematode, Ditylenchus dipsaci, is a plant-parasitic nematode affecting over 500 plant species worldwide. Since 2012, garlic producers from Ontario and Quebec have been particularly affected with economic losses caused by this pest. Reproduction of D. dipsaci on a particular host depends on its biological race, and races are unknown for these populations from eastern Canada. As a polyphagous pest, D. dipsaci can possibly be a threat and have negative impact on many crops grown in Quebec, such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 19 publications
2
5
0
Order By: Relevance
“…Consistent with our results, reproduction factor of garlic as control plant was higher than 6 (excellent host) and wheat was less than 1 (non-host). Recently, Poirier et al (2019) reported barley, carrot, lettuce and maize as non-hosts for a garlic population of D. dipsaci from Canada, and therefore useful for rotation in D. dipsaci-infested garlic production areas in Canada, these results are similar to our results. They also found the nematode reproduced well on garlic and onion, and less well on potatoes, as we found in our study.…”
Section: Susceptibility Of Plant Speciessupporting
confidence: 92%
“…Consistent with our results, reproduction factor of garlic as control plant was higher than 6 (excellent host) and wheat was less than 1 (non-host). Recently, Poirier et al (2019) reported barley, carrot, lettuce and maize as non-hosts for a garlic population of D. dipsaci from Canada, and therefore useful for rotation in D. dipsaci-infested garlic production areas in Canada, these results are similar to our results. They also found the nematode reproduced well on garlic and onion, and less well on potatoes, as we found in our study.…”
Section: Susceptibility Of Plant Speciessupporting
confidence: 92%
“…In a recent study (Poirier et al, 2019) in Canada, lucerne and lettuce were found to be non-hosts of a garlic population of D. dipsaci, similar to our study. Also, consistent with the findings of the present study, Hajihassani et al (2016) reported that wheat was a non-host, chickpea cultivars were poor hosts and garlic a good host.…”
Section: Discussionsupporting
confidence: 91%
“…This study did not aim to determine the biological race of the four D. dipsaci populations. A host preference investigation is, to date, the only way to determine a D. dipsaci population's biological race (Poirier et al, 2019). An easy method to determine the biological race of field population would help growers to adapt their crop rotation and reduce nematode pressure by avoiding host plant species.…”
Section: Discussionmentioning
confidence: 99%
“…The reproduction of polyphagous races varies greatly among host plant species (Whitehead et al, 1987). Qiao et al (2013) and Poirier et al (2019) reported distinct genotypes among D. dipsaci populations within a geographic region and between neighboring farms. Esquibet et al (1998) succeeded to molecularly distinguish the species D. dipsaci sensu lato from the giant race D. gigas, recently singled out as new species (Vovlas et al, 2011).…”
Section: Introductionmentioning
confidence: 99%